An overview of corporate income tax in South Africa - Ramsunder, Julita (My University, 2022)
This paper investigates the corporate income tax regime in South Africa in order to determine if it has a comparatively high cost corporate tax regime compared to other jurisdictions. The paper also explores the relationship between corporate income tax and investment, as a higher tax cost relative to other jurisdictions is likely to discourage investment in South Africa. The paper uses three different measures to compare South Africa to other jurisdictions namely: the statutory rate, the backward effective rate and the forward effective rate. South Africa has a relatively high statutory rate, forward and backward effective tax rate which suggests the country imposes a higher corporate income tax cost compared to other jurisdictions in the sample. In South Africa, economic growth is key for driving both corporate tax collections and investment, where certain studies suggest that economic conditions are far more important than the tax structure for investment decisions. Further studies are required to fully unpack the investment and tax regime relationship in South Africa.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Commerce to the Faculty of Commerce, Law and Management, University of the Witwatersrand, Johannesburg, 2022
Keywords: Corporate Income Tax Regime; South Africa; Regulatory Development